Analisis Pengaruh Promosi, Live Streamers, Dan Tekanan Waktu Terhadap Keputusan Pembelian Pada Fitur Shopee Live - Mulyadi, Ari Dian Safitri; Nurhasanah, Saniatun (Universitas Negeri Surabaya, 2024)
This research analyzes the influence of promotions, live streamers, and time pressure on purchasing decisions made through the Shopee Live feature. The method employed in this study is quantitative descriptive. This research's population and sample size totaled 193 individuals in Jabodetabek Area. The sampling technique utilized is probability sampling with purposive sampling. The statistical analysis conducted in this research employed Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The research findings indicate that promotions have a significant positive effect on purchasing decisions through the Shopee Live feature. Additionally, live streamers exert a significant positive influence on purchase decisions via the Shopee Live feature. Moreover, time pressure demonstrates a significant positive effect on purchasing decisions through the Shopee Live feature. The Shopee Live feature is expected to increase effective promotional strategies, namely personal sales and direct marketing carried out by live streamers, so that customer awareness of the Shopee Live feature continues to increase, thereby influencing purchasing decisions. Furthermore, the Shopee application is expected to provide more sales promotions and also provide time limits when conducting live streaming.